FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK PADA PERUSAHAAN GO PUBLIC DI INDONESIA TAHUN 2008-2011 - Mita Ardayani, 09.05.52.0088; Aini, Nur (Students Journal of Accounting and Banking, 2014)
The main purpose of this research is examining the effects of audit opinion, management changes, KAP size, firm size and financial distress to auditor changes. Some former research about auditor changes show different result each other. Because of that, it is important to do repetitively research to verificate the theory about auditor changes. This research is using data of go public company in Indonesia in the period 2008â2011. The researcher uses purposive sampling and get total sample are 104 research data. The data is examined with logistic regressin in SPSS 19 software to examine the effect of audit opinion, management changes, KAP size, firm size and financial distress to auditor changes. Result of this research show that management changes has significant effect on auditor changes. However management changes has the opposite direction with the research hypothesis that can not support the hypothesis, while other factors like audit opinion, KAP size, firm size and financial distress do not have significant effect on auditor changes. Keywords: Auditor changes, audit opinion, management changes, KAP size, firm size and financial distress